Perbandingan Pelepasan Mikroplastik Ke Udara Pada Miniatur Bangunan Dengan dan Tanpa Material Daur Ulang Sampah Plastik - Tri Marthy Mulyasari; Nur Hilal; Yudhiakuari Sincihu (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2026)
The utilization of plastic waste as an alternative raw material in construction products has emerged as a promising strategy to reduce plastic waste generation. However, plastic waste-based construction materials may act as a source of airborne microplastic release, potentially affecting environmental quality and human health through inhalation exposure. This study aimed to analyze the quantity of airborne microplastics in buildings constructed with plastic waste-based materials compared to control buildings without plastic waste-based materials. A comparative descriptive study was conducted using two miniature building models consisting of a control building and a building constructed from plastic waste materials. Airborne microplastic sampling was carried out using an air suction device over a 60-day observation period and were microscopically analyzed to determine the quantity of microplastics with particle sizes ≥2.5 µm. Data were analyzed descriptively and presented as minimum, maximum, mean, and standard deviation values. Microplastics were detected in all air samples collected from the miniature buildings. In the control group (n= 60), airborne microplastic concentrations ranged from 11 to 28 particles/samplel, with a mean of 22.00 ± 3.99 particles/sample. In the treatment group constructed with plastic waste-based materials (n = 60), airborne microplastic concentrations ranged from 26 to 72 particles/sample, with a mean of 38.78 ± 9.78 particles/sample. The results indicated that the average quantity of airborne microplastics in buildings constructed with plastic waste-based materials was substantially higher than that observed in the control buildings. Buildings constructed with plastic waste-based materials generated higher levels of airborne microplastics than buildings without plastic waste-based materials. These findings suggest that plastic waste-based construction materials may serve as a potential source of airborne microplastic release. Further studies are needed to characterize the released microplastics and evaluate their potential health risks under more representative building conditions.